Template-free synthesis of hierarchical porous anatase TiO2 microspheres with carbon coating and their electrochemical properties - Permana, Antonius Dimas Chandra; Nugroho, Agung; Chung, Kyung Yoon; Chang, Wonyoung; Kim, Jaehoon (ELSEVIER SCIENCE SA, 2014)
Hierarchically porous anatase titanium oxide (TiO2) microspheres were synthesized using a green supercritical methanol route over a very short reaction time of 15 min without using templates or surfactants. Primary nano-sized particles with diameters of 20-55 nm with organic coverage on the surface were loosely aggregated and formed secondary micron-sized particles 1.0-2.5 mu m in diameter, creating a porous structure with average pores 9-15 nm in diameter. When the as-synthesized microspheres were calcined under a Ar/5% H-2 condition, carbonization of the organic groups formed an ultrathin and uniform carbon layer on the nano-sized primary particles with a thickness of 0.5-1 nm and reduced some of the Ti4+ to Ti3+. Both the hierarchically porous structure and the conductive layer coating had positive effects by increasing Li ion storage capacity. The prepared TiO2 microspheres exhibited a high reversible discharge capacity of 212.3 mA h g(-1) at 0.1 C, a high-rate performance of 77.9 mA h g(-1) at 8 C, and an excellent capacity retention of >97% at the end of 100 cycles at 1.0 C, whereas TiO2 nanoparticles without porous structure and surface modification exhibited lower discharge capacities of 161.8 mA h g(-1) at 0.1 C and 5.2 mA h g(-1) at 8 C, and poorer capacity retention of 26%. The considerable improvement in the electrochemical performance was attributed to the nano-sized TiO2 primary particles, porous structure, and carbon coating and Ti3+ incorporation. Crown Copyright (C) 2013 Published by Elsevier B.V. All rights reserved.
Keywords: LI-ION BATTERIES; CONTINUOUS HYDROTHERMAL SYNTHESIS; METAL-OXIDE NANOPARTICLES; HIGH-RATE PERFORMANCE; PROMOTED H-DONATION; SUPERCRITICAL WATER; LITHIUM-STORAGE; NANOSTRUCTURED MATERIALS; SOLVOTHERMAL SYNTHESIS; MESOPOROUS ANATASE